An insight into metal organic framework derived N-doped graphene for the oxidative degradation of persistent contaminants: formation mechanism and generation of singlet oxygen from peroxymonosulfate. Issue 2 (16th January 2017) - Liang, Ping; Zhang, Chi; Duan, Xiaoguang; Sun, Hongqi; Liu, Shaomin; Tade, Moses O.; Wang, Shaobin
Abstract : Singlet oxygen produced during peroxymonosulfate activation by N-graphene dominated the pollutants degradation. Abstract : The synthesis of carbonaceous materials from a metal organic framework (MIL-100), organic linker and N-precursor was comprehensively investigated, and the structures of the products were characterized. It was found that simple pyrolysis of mixed MIL-100 (Fe)/dicyandiamide (DCDA) could produce nitrogen-doped graphene (N-graphene). The N-graphene showed excellent performances in peroxymonosulfate (PMS) activation, which were superior to those of counterparts of graphene, iron(ii, iii ) oxide, manganese(iv ) oxide and cobalt(ii, iii ) oxide. With PMS activation, N-graphene exhibited efficient catalytic degradation of various organic pollutants such as phenol, 2, 4, 6-trichlorophenol (TCP), sulfachloropyridazine (SCP) and p -hydroxybenzoic acid (PHBA). Electron paramagnetic resonance (EPR) spectroscopy and radical quenching tests were employed to investigate the PMS activation and organic degradation processes. It was found that singlet oxygen ( 1 O2 ) was mainly produced during the activation of PMS by N-graphene, and contributed to the catalytic oxidation instead of sulfate and/or hydroxyl radicals. These findings provide new insights into PMS activation by metal-free carbon catalysis.